2001
DOI: 10.1007/bf02287230
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of adolescent mental health service use

Abstract: This study examines longitudinal mental health service use patterns of a school-based sample of adolescents. Based on the Center for Epidemiologic Studies Depression Scale scores, a stratified sample of middle-school students was interviewed using the Schedule for Affective Disorders and Schizophrenia for School-Aged Children: cycle one (n = 579; mean age 12.83) and cycle two (n = 490; mean age 18.65). Service use also was assessed by mailed questionnaire: cycle three (n = 330; mean age 20.60). Service use dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 19 publications
1
45
1
Order By: Relevance
“…Findings from Cuffe et al (2001) suggest that gender may influence mental health service use in depressed youth. Among 19-24 year olds, females were more likely than males to access mental health services (Lin et al 1996;Leaf et al 1985;Bland et al 1997;Rhodes et al 2002).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Findings from Cuffe et al (2001) suggest that gender may influence mental health service use in depressed youth. Among 19-24 year olds, females were more likely than males to access mental health services (Lin et al 1996;Leaf et al 1985;Bland et al 1997;Rhodes et al 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Among 19-24 year olds, females were more likely than males to access mental health services (Lin et al 1996;Leaf et al 1985;Bland et al 1997;Rhodes et al 2002). However, some studies show that gender may not have a significant impact on mental health service use when respondents under age 19 are sampled (Cuffe et al 2001;Zwaanswijk et al 2003;Verhulst and van der Ende 1997).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…One study reported that only 30% of children who used services during a 3-month period continued to use services during the subsequent 3-month period and fewer than 10% of children persisted in service use across multiple 3-month follow ups (Farmer et al 1999). Similarly, a longitudinal study reported that the percent of individuals receiving mental health treatment in the past year started at 24% and decreased to 3% by the end of the 7-year study (Cuffe et al 2001). The most common pattern of service use for both outpatient specialty mental health services and educational services is 1-2 visits over a 3-month period (Farmer et al 1999).…”
Section: Introductionmentioning
confidence: 92%